PID Control Design for Biofuel Furnace using Arduino - Agus Budianto; Wahyu S. Pambudi; Sumari Sumari; Andik Yulianto (Universitas Ahmad Dahlan, 2018)
The target of the Indonesian government in 2025 is increasing the use of renewable energy up to 23%, one part of potential renewable energy in Indonesia is biofuel. Biofuel requires raw materials of plant or animal oil with or without catalyst, it does not require the raw material of ethanol or methanol. The product is similar to gasoline and diesel that came from crude oil. Potential oil-producing plants in Indonesia are Palm Oil and Nyamplung (Calophyllum inophyllum L.). The process of making biofuel from this material is done by heating the reactor or furnace with temperature range of 350° C - 500° C. To reach the stability of furnace temperature, it requires temperature control systems and one of them is PID. Arduino microcontroller is an open source and user friendly platform for hardware and software. The control system that designed by using arduino is capable to control the furnace temperature from 200° C to 400° C and it is using a 6000 watt heater. The best system response is achieved when Kp = 15, Ki = 15 and Kd = 1. With these parameter values, the system has the lowest overshoot response of 16%, so it is safe for biofuel furnace, even though the rise time value is 146 s, settling time of 429 and steady state error is equal to 2.87%.